Philosophy and Ideology in John 9-10 Read as a Single Literary Unit - Engberg-Pedersen, Troels (Histos, 2013)
The article argues for five connected theses: (1) that against some older, quite established perceptions, but in line with a more recent trend, chapters 9–10 of the Fourth Gospel should be seen as a single literary unit, held together by a concern with a single motif: how to draw the proper conclusion about Jesus’ identity from his acts (ἔργα), that is, understanding them as ‘signs’ (σηµεῖα); going beyond the recent trend, the article claims that this single unit includes John 10:22–42, which scholars regularly see as independent; (2) that the text’s articulation of ἔργα as σηµεῖα may be fully grasped once one sees it in the light of the Stoic theory of the ‘sign’ (σηµεῖον); (3) that the literary unity focused on the ability to read Jesus’ ἔργα as ‘signs’ yields a thematic unity of the two chapters, which consists in the contrast between those able to do the proper reading (the blind man healed representing Christ-believers more generally) and those unable to do so (‘the Jews’); (4) that the text operates centrally with the idea of behaving violently towards the other part and that it unilaterally ascribes the initiative for this to ‘the Jews’; (5) that this move is an ‘ideological’ one.